Case Report: Variety of Target Antigens During 1 Year Follow-Up of a Patient Initially Diagnosed With Bullous Pemphigoid - Qian, Hua; Zhou, Zhijun; Shi, Luhuai; Li, Huicheng; Liu, Weijun; Ai, Yong; Gao, Yangmin; Feng, Suying; Hashimoto, Takashi; Li, Xiaoguang (Frontiers in Immunology, 2022)
Autoimmune bullous diseases (AIBDs), presenting cutaneous and/or mucosal bullous lesions, are classified into pemphigus and pemphigoid diseases. Long time observation for complicated AIBD cases is rarely reported. In this study, serum samples of one AIBD patient were collected at 7 different time points during the disease course including a relapse, which were examined by our conventional and newly developed methods for the detection of autoantibodies. Interestingly, we found changes of both the presence and the titers of various autoantibodies in accordance with changes of clinical features during the whole disease course, which indicated that the patient started as bullous pemphigoid and relapsed as concurrence of bullous pemphigoid and mucosal-dominant-type pemphigus vulgaris.